Surgical treatment of chronic thromboembolic pulmonary hypertension in combination with a left anterior descending artery myocardial bridge: A case report - Zugurov, Ilkhom K.; Osadchii, Aleksei M.; Simakova, Maria A.; Moiseeva, Olga M.; Gordeev, Mikhail L. (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary thromboendarterectomy is a potentially curative option for most patients with chronic thromboembolic pulmonary hypertension (CTEPH). However, a special group of patients with CTEPH requires simultaneous cardiac procedures. We report a rare case of successful surgical treatment of a CTEPH patient with a left anterior descending artery myocardial bridge. Despite the complexity of performing pulmonary thromboendarterectomy (PTE), the issue concerning the method of revascularization of the artery in the case of the left anterior descending artery myocardial bridge is controversial. PTE and supracoronary myotomy were performed. In our case, the optimal surgery method for the left anterior descending artery myocardial bridge was chosen intraoperatively based on the depth and length of the myocardial bridge. The patient's significant functional improvement after surgery and hemodynamic normalization were confirmed at the follow-up assessment. This case demonstrates rare but potentially dangerous pathologies that can be treated with minimal adverse effects.